A user-oriented view of "learning environment". (11th May 2004) - Caroli, Folker; Hauenschild, Christa; Wagner, Daniela
Within the rapid development that e-learning has taken in the last years, we still recognise a tendency of restricting the discussion to technical issues. This also influences the way in which e-learning environments are looked upon. What is expected from the users (teachers as well as students) is mostly technical competence in handling them. Our experience in several virtual seminars in the context of the project "Virtueller Campus Sprache – Wissen –Information", however, shows that this is an inadequate view for an successful exploitation of the potential of computer supported collaborative learning. In our paper, we want to discuss a broader concept of "learning environments" including especially social structure and working phases and therefore presupposing communicative competence of their users. From this concept, we derive the essential elements of a learning environment in our wide sense of the term and we discuss requirements for the technical infrastructure supporting this kind of e-learning.